Case report: Comprehensive clinical, pathological and genetic investigations to decipher the background of cyclic thrombocytopenia - Zsófia Flóra Nagy; Kristóf Árvai; Péter Lakatos; Ildikó Beke Debreceni; Balázs Szili; Ildikó Istenes; Csaba Bödör; Judit Demeter (Frontiers Media S.A., 2024)
Cyclic thrombocytopenia (CTP) is a rare disease characterized by the oscillations seen in the platelet count of the patients. The pathomechanism of the disease is poorly understood, several pathological processes have been implied in the background of CTP. In our current study, we aimed to thoroughly investigate the case of a 41-year-old female patient with a 22-year history of CTP. Wide-ranging laboratory testing, histological analyses and genetic investigations were carried out to investigate all the defects and alterations of physiological pathways described in the background of CTP to date. Bone marrow biopsy showed normal hemopoiesis with the abundance of megakaryocytes, some of which displayed hypolobulated nuclei. T-cell receptor rearrangement studies showed a polyclonal pattern with no indication of a monoclonal cell population. Flow cytometric assessment of the platelets revealed large number of immature platelets and decreased expression of glycoprotein IIb and IIIa at platelet zenith. Increased expression of glycoprotein IIb, IIIa and glycoprotein Ib-IX complex was observed at the nadir of the cycle. Whole exome sequencing revealed a heterozygous missense variant of uncertain significance in the SERPINC1 gene, which has been associated with hereditary antithrombin deficiency. The screening of autoantibodies did not reveal signs of autoreactive processes, and no thyroid dysfunction was found. Furthermore, synchronization with the menstrual cycle could not be concluded based on our patient's case. With our results we contribute to the very limited data known about the long-term course of the disease and provide valuable insights into the genetic architecture of CTP.